1999
DOI: 10.1093/jjco/29.9.425
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Demonstration of Cytokeratin is Useful for Detecting Micrometastatic Foci from Gallbladder Carcinoma in Regional Lymph Nodes

Abstract: Cytokeratin staining of dissected lymph nodes is a useful new diagnostic tool for detecting micrometastatic foci in regional lymph nodes of patients with gallbladder carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…KL-1 reacts with cytokeratins (CK), components of intracytoplasmic network of intermediate filaments (Ifs) [4,8,35] , specifically reacts with epithelial tumors. Anti-CK mABs using immunocytochemistry or CK RT-PCR have been widely used for the detection of micrometastases in lymph nodes, venous blood and bone marrow [1,4,12,28,[36][37][38][39][40][41][42] . It is satisfactory using KL-1 monoclonal antibody to detect micrometastasis in the lungs and livers of the mice in this study.…”
Section: Discussionmentioning
confidence: 99%
“…KL-1 reacts with cytokeratins (CK), components of intracytoplasmic network of intermediate filaments (Ifs) [4,8,35] , specifically reacts with epithelial tumors. Anti-CK mABs using immunocytochemistry or CK RT-PCR have been widely used for the detection of micrometastases in lymph nodes, venous blood and bone marrow [1,4,12,28,[36][37][38][39][40][41][42] . It is satisfactory using KL-1 monoclonal antibody to detect micrometastasis in the lungs and livers of the mice in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Other series using either cytokeratin subtype 7 or 8/18 have also shown that cytokeratin immunostains are highly sensitive in detecting BD and GB cancers [17][18][19]. Both EMA and CEA were less appealing as immunostains, because of weaker staining in histologically positive BD and GB cancers (Figs.…”
Section: Discussionmentioning
confidence: 96%
“…The incidence of micrometastases in patients with breast, melanoma, or GI cancers ranges widely, between 10% and 50%, and the clinical significance of this finding is highly variable between studies [8, 10, 14 -16]. Unfortunately, only a few studies have evaluated the incidence and clinical significance of lymph node micrometastases in patients with biliary tract carcinoma [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Tiny aggregates of cancer cells can be detected by means of cytokeratin immunohistochemistry in histologically negative lymph nodes (Yokoyama et al 1999;Natarajan et al 2005;Sasaki et al 2006). In one study, 7 out of 255 HE-negative lymph nodes (2.7 %) were found to be positive for micrometastases by the use of cytokeratin immunostaining (Tajima et al 1999). …”
Section: Lymph Node Metastasesmentioning
confidence: 99%